Online Requirements and Portal Design for Female University Science and Technology Students in Kenya - (:unkn) unknown (My University, 2013)
In science and technology (S&T) career progression, women drop out at virtually every step until extremely few are found in positions of influence and recognition. Although this is a global problem, it is even more critical in Africa. The number of female university S&T students in Africa has remained low for the past about three decades. There is thus a dire need to encourage/support such students especially in African countries, including Kenya. Online portals have the potential to motivate/support Kenyan female university S&T students. It is however critical to understand the characteristics and requirements of these students. While there exists literature on the differences between online female users and male users, women in S&T in African countries (including Kenya) face rather unique challenges. This paper reports a study that indicates the characteristics and online requirements of Kenyan female university S&T students, and then describes a corresponding online portal design.
Keywords: African Research